Effect of Moxibustion Therapy on Intensity of Primary Dysmenorrhea in Adolescents Girl at Cimahi Negeri 2 Junior High School - Roswendi, Achmad Setya (KnE Life Sciences, 2021)
Based on the data from the World Health Organisation (WHO), primary dysmenorrhea is prevalent among 55-75% adolescent girls and women of reproductive age. Threequarters of these women experienced mild-moderate dysmenorrhea. One of the non-pharmacological treatments for dysmenorrhea is moxibustion therapy. The heat from moxa is able to stimulate sensory nerve cells around the acupoints and can affect the endocrine system to release endorphins and also inhibit pain impulses in spinal cord. This research design was quasi-experiment with non-equivalent control group design, using non-probability with purposive sampling technique, which obtained 54 samples consisting of 27 in each intervention and control groups. Mean was used in univariate analysis and t-dependent also t-independent tests was used in bivariate analysis. This research occured at Cimahi Negeri 2 Junior High School. In the intervention group the therapy was given in one-time, 1 inch above the 9 acupoints within 15 minutes long, while in the control group no intervention was given. The results of the study proved the differences in the mean pain scale values of primary dysmenorrhea in the intervention group and the control group (p-value = 0.000) so that there is an effect of moxibustion therapy on the intensity of primary dysmenorrhea in adolescents. Moxibustion therapy can be recommended to be applied as a non-pharmacological action to treat dysmenorrhea and can be done independently. Keywords: Acupoints, Moxibustion Therapy, Primary Dysmenorrhea